Increased spatial dimensions of repetitive heat and cold stimuli in older women. Issue 5 (May 2017) - Naugle, Kelly M.; Cruz-Almeida, Yenisel; Fillingim, Roger B.; Staud, Roland; Riley, Joseph L.
Abstract : Abstract: Protocols of temporal summation (TS) of pain typically involve the delivery of brief repetitive noxious pulses of a constant intensity while measuring the perceived intensity of pain after each pulse. The size percept of noxious repetitive stimulation has been poorly characterized. Furthermore, no studies have investigated age differences in TS of cold pain. The current study examined TS of pain intensity and the perceived size of the painful area during repetitive noxious heat and cold pulses in healthy younger (n = 104) and older adults (n = 40). Trials of 10 brief repetitive noxious heat or cold pulses were delivered to the upper extremities. Participants rated the perceived size of the painful area or intensity of pain after each pulse. The magnitude of change for the size percept and intensity for pain were calculated for each trial. The results indicated that older adults experienced greater TS of the size percept of cold stimuli compared with younger adults. Additionally, older women experienced greater TS of the size percept of heat stimuli compared with older men and all younger participants. No overall age or sex differences were found in the TS of pain intensity for cold or heat trials. These results suggest dysfunctional modulation of the spatial percept of the painful stimuli by older adults, and in particular older women, during repetitive noxious thermal pulses. Abstract : This study found that older women experience greater spatial summation of pain than older men and all younger adults, and particularly for painful cold.